“The Boundless Realm Where All Form Lies”. Representing Imagination at the Crossway Between Literary and Neurocognitive Studies - Gambino, Renata; Pulvirenti, Grazia (Frontiers in Integrative Neuroscience, 2021)
According to ancient texts on poetics, the concept of representation is deeply bound to that of “mimesis;” this last was intended in two main ways: as “imitation” and as “world construction.” In Aristotle's Poetics, mimesis is theorized as the main form of “world simulation,” giving rise to the complex universe of fiction. The concept of simulation plays a pivotal role in the neurocognitive theories on the embodied mind: within this frame, embodied simulation is intended as a functional prelinguistic activation of the human sensorimotor mechanism. This happens not only with regard to intercorporeality and intersubjectivity in the real world but also in relation to the process of imagination giving rise to literary imagery and to the reader's reception of the fictional world, since human beings share a common sensorimotor apparatus. Imagination is a central concept in the recent neurocognitive studies since it plays a core role in human life and in artistic production and reception. Imagination has been considered as a complex emergent cognitive faculty deeply intertwined with perception, memory, and consciousness, shaping human life and transforming the limited horizon of our perceptual affective understanding, being, and acting. Although there is an immense bulk of literature on this topic, imagination is still an elusive concept: its definition and understanding change according to different heuristic frames—mainly the philosophical, aesthetic, poetic, and cognitive ones—giving rise to debates about its modalities and effects, particularly in relation to the construction of aesthetic and symbolic constraints. In this paper, we claim that scientific research may take advantage from the literary representation of the imaginative faculties, which occurs in specific tests characterized by dynamic images and motion. In such meta-representation of the imagination, we witness the phenomenological emergence of endogenous dynamic processes involving a cluster of cognitive faculties, activated by triggering the reader's embodied simulation. One of the main German poets, Johann Wolfgang von Goethe, in the second part of his masterwork Faust II, intuitively represents the very process of the imagination and its responding to embodied simulation with regard both to the author's creative act and to its reception by the reader. At the crossway between literary and neurocognitive, this study aims to highlight the advantage offered to future transdisciplinary inquiries by the literary representation showing features and dynamics of the still mysterious phenomenon of the imagination.